PENATALAKSANAAN FISIOTERAPI PADA HERNIA NUCLEUS PULPOSUS (HNP) LUMBAL DENGAN MODALITAS SHORTWAVE DIATHERMY (SWD), TRAKSI DAN MC. KENZIE EXERCISE DI RSUD BENDAN KOTA PEKALONGAN - Azinudin Arkan; Irine Dwitasari Wulandari (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2022)
Hernia Nucleus Pulposus (HNP) is a disorder that involves rupture of the annulus pulposus (outer ring of the disc) so that the nucleus pulposus protrudes (hernias) and compresses the spinal nerve root, causing pain and possibly neurologic deficits. Most occur between L4 and L5, compressing the L5 nerve root or between L5 and S1, pressing the S1 nerve root. The purpose of this study was to determine the effect of Physiotherapy Management on Lumbar Hernia Nucleus Pulposus (HNP) with Shortwave Diathermy (SWD), Traction and Mc. Kenzie Exercise. The study was conducted at Bendan Hospital, Pekalongan City with descriptive analytic with Hernia Nucleus Pulposus (HNP). Methods of collecting research data using auto anamnesis and physical examination. The research instruments consisted of examining pain with a visuale analogue scale (VAS), muscle spasm with palpation, muscle strength with manual muscle testing (MMT), joint range of motion with a goniometer and midline and functional activity with a oswestry disability index (ODI). After therapy 1 to therapy 4 there was a decrease in pain from T1 = silent pain 2, tenderness 5 and motion pain 7 to T4 = silent pain 0, tenderness 1 and motion pain 4. Decreased muscle spasm T1 = 1 to T4 = 0. Increased muscle strength T1 = flexor 3, extensor 3, lateral flexor dextra 3, lateral flexor sinistra 3 and rotator 4 to T4 = flexor 4, extensor 4, lateral flexor dextra 4, lateral flexor sinistra 4, rotator dextra 5, rotator sinistra 5. Increased range of motion the joint from T1 = 44 cm flexion, 34 cm extension, 48 cm lateral flexion dextra, 48 cm lateral flexion sinistra, 45⁰ rotation dextra, 45⁰ rotation sinistra. Increased functional activity from T1 = 40% (moderate disability) to T4 = 30% (moderate disability). The conclusion of this research is giving Shortwave Diathermy (SWD), Traction and Mc. Kenzie Exercise can reduce pain, reduce muscle spasm, increase muscle strength, increase joint range of motion and increase functional activity.